Ten journeys to Cameron's farm : an Australian tragedy - Hazlehurst, Cameron, 1941- (ANU.Lives series in biography., 2013)
Three decades after what he called 'a dreadful air crash, almost within sight of my windows' Robert Menzies wrote 'I shall never forget that terrible hour; I felt that for me the end of the world had come ... ' Ten Journeys to Cameron's Farm tells the lives of the ten men who perished in Duncan Cameron's Canberra property on 13 August 1940: three Cabinet ministers, the Chief of the General Staff, two senior staff members, and the RAAF crew of four. The inquiries into the accident, and the aftermath for the Air Force, government, and bereaved families are examined. Controversial allegations are probed: did the pilot F/Lt Bob Hitchcock cause the crash or was the Minister for Air Jim Fairbairn at the controls? 'Cameron Hazlehurst is a story-teller, one of the all-too rare breed who can write scholarly works which speak to a wider audience. In the most substantial, original, and authoritative account of the Canberra aircraft accident of August 1940 he provides unique insights into a critical, poignant moment in Australian history. Hazlehurst's account is touched with irony and quirks, set within a framework of political, social, and military history, distinctions of class, education, and rank, and the machinations of parliamentary and service politics and of the 'official mind'. The research is meticulous and wide-ranging, the analysis is always balanced, and the writing at once skilful and compelling. This is a work of an exceptional historian.' (Ian Hancock, author of Nick Greiner: A Political Biography, John Gorton: He Did It His Way, and National and Permanent? The Federal Organisation of the Liberal Party of Australia) 'Ten Journeys to Cameron's Farm is a monumental work of historical research pegged on a single, lethal moment at the apex of government at an extraordinarily sensitive time in Australia's history. The book embodies top drawer scholarship, deep sensitivity to antipodean class structures and sensibilities, and a nuanced understanding of both democratic and bureaucratic politics.' (Christine Wallace, author of Germaine Greer Untamed Shrew and The Private Don: the man behind the legend of Don Bradman).